Numerical simulation to improve robustness in sheet metal forming process chains - Hagenah, Hinnerk; Geiger, Manfred; Merklein, Marion (AIP Conference Proceedings, 2013)
The paper will present developments towards the improvement of the robustness of sheet metal forming process chains. The possibilities and challenges will be demonstrated using two examples. Firstly, the effect of heat treatment to precipitation hardened aluminum sheet metals in order to enlarge the process window for deep drawing operations will be discussed. Numerical simulation can be used to predict the effects of the heat treatment. Using more sophisticated approaches the heat treatment layout and its effects on the forming process can be computed and predicted. Thus the process window can be enlarged and in consequence the process chain will receive an increased robustness. Secondly the integrated tube and sheet hydroforming process that also includes joining operation will be used as an example of the positive impact numerical simulation can have on complex process chains. This highly integrated process chains needs carefully designed tools that ensure robust production. Furthermore, several effects occurring during the forming operations are difficult to understand since the process cannot be stopped at arbitrary moments or easily investigated in situ. The needed understanding and therefor the mandatory input for successful and robust process design has to be derived from advanced numerical models and the according simulation runs. © 2013 AIP Publishing LLC.
LFT Import::2019-07-29 (1899)
Keywords: Robust process chains; sheet hydroforming; tailored heat treatment